A Study on The Effectiveness of Bentonite Adsorbent in Reducing Pb Metal Levels in Used Lubricating Oil - Satoding, Gain Allegra; Ardiansah, Ardiansah; Albar J, Muh. Azis; Sumbung, Jony (Jurnal Sains dan Teknik Terapan, 2024)
Used lubricating oil contains contaminants that can pollute the environment if not managed properly. One of the contaminants contained in it is heavy metals. Adsorption using adsorbent materials such as bentonite has become one of the commonly used methods for removing contaminants in used lubricating oil. Bentonite is a clay that is good for use as an adsorbent for heavy metals because it has large enough particles that are good for absorbing them. However, the effectiveness of bentonite adsorption can be influenced by the mass of bentonite used in the process. This research aims to determine the effectiveness of the influence of bentonite mass on reducing Pb metal in lubricating oil using HCl-activated bentonite. The research results show that increasing the mass addition of bentonite can increase the effectiveness of adsorption and the removal efficiency of Pb metal in used lubricating oil. This is characterized by a decrease in Pb metal content in used lubricating oil before and after the adsorption process, namely in sample A with the addition of 2 grams. The Pb metal content in used lubricating oil is 0.2471 ppm, 4 grams is 0.2000 ppm, 6 grams is 0.142 ppm, at 8 it was 0.0895 ppm, and at 10 grams it was 0.0316 ppm. In sample B, with the addition of 2 grams, the metal content of Pb in the used lubricating oil was 0.3000 ppm, 4 grams was 0.2474 ppm, 6 grams was 0.2053 ppm, 8 grams was 0.1474 ppm, and 10 grams was 0.0684 ppm.